The effect of Plant Growth Promoting Rhizohacteria on activities of antioxidative enzymes, physiological characteristics and root growth of four chickpea (Cicer arietinum L.) cultivars under dry land conditions of Ilam privince - Rahim Naseri; Abbas Soleymani Fard; Amir Mirzaei; Fereshteh Darabi; Amin Fathi (پژوهش‌های حبوبات ایران)
Introduction Chickpea is widely cultivated as an important cool season grain legume crop throughout the world. According to FAO, Iran is one of the major chickpea (Cicer arietinum L.) producing countries in the world. In Iran, chickpea is the most important pulse crop with respect to production and area under cultivation. This crop is cultivated in about 500,000 ha, of which over 95 percent are grown under rainfed conditions. Average chickpea yield in Iran is about 400 to 600 kg.ha−1, that is well below the world average of 900 kg.ha−1. Drought and high temperature are two major factors limiting the growth and productivity of chickpea during summer in many regions. Drought stress is common in many parts of the world and more than 50% of the globe is arid or semi arid and plants are subjected to some level of drought stress. Drought stress can adversely affect plant growth and production. Plant response to drought stress, at cellular and molecular level, limits plant growth and yield. It has been shown that several PGPR can support plants by producing antioxidant factors or modulate photosynthesis decreasing ROS and thus lowering the need for antioxidant activity during stress which could explain why primed plants tend to decrease their own antioxidant defense system. Over reduction of the photosynthetic electron transport chain induces the generation of reactive oxygen species (ROS) such as singlet oxygen (1O2), superoxide anion (O2•-), hydrogen peroxide (H2O2), and hydroxyl radical (•OH). Therefore, the decline in growth and productivity due to these stress factors is associated with increased levels of ROS, which cause damage to cellular structures and macromolecules. In order to maintain or increase crop productivity it becomes necessary to evolve efficient low-cost technologies for abiotic stress management. It is now a priority area research for developing strategies to cope with abiotic stresses including development of stress tolerant varieties, shifting crop calendars, resource management practices etc. However, most of these techniques are cost-intensive and time taking. Recent studies indicate that soil microorganisms can help crops withstand abiotic stresses more efficiently. These include tolerance to salt and water stress (Azospirillum sp., Pseudomanas sp, Bacillus sp). The increased H2O2 content under stress conditions led to lipid peroxidation, which is widely used as an indicator of stress-induced oxidative damage. The relative water content (RWC) and lower electrolyte ion leakage (EL) in plants exposed to drought has been considered indicative of a relative tolerance to water stress. In our study, RWC declined while %EL increased in both inoculated and uninoculated seedlings under drought stress compared to normal irrigation. However, bacterial inoculation did help plants to increase their RWC and to decrease their %EL as compared with uninoculated plants in drought stress. Investigations involving wheat species and varieties have detected increases in the activity of superoxide dismutase (SOD), catalase (CAT), and non-specific peroxidase (guaiacol peroxidase, POD). The main objective was to evaluate the effects of Plant Growth Promoting Rhizohacteria on activities of antioxidative enzymes, physiologic traits and root growth of chickpea in dry land conditions of Ilam province.